(untitled) (El Hilo de la Fabula, 2020)
This article aims to reflect is to reflect on the transnational dimension of many contemporary authors in Italy and within the framework of the European context. Transnationalism assigns a pivotal role to the construction of a cross–border or hybrid imagination, on different cultural and communicational levels, for example by encouraging the attention to those productions in the literary, cinematic, and artistic field which would be unthinkable if we relied on the traditional concept of space where physical, cultural, political and social geography are perfectly matched. The paradigm of transnationalism also sheds light on the productions of contemporary literary authors who have multicultural and multilingual backgrounds, live and operate in a specific national context or in different periods, move from one nation to another, or even follow intercontinental trajectories.